Quantitative Assessment of Soluble Fibrin in Plasma by Affinity Chromatography – A Comparative Study with desAA-Fibrin, desAABB-Fibrin and Fibrinogen - Thiel, Wilfried; Delvos, Ulrich; Müller-Berghaus, Gert (Thrombosis and Haemostasis, 1985)
A quantitative determination of soluble fibrin in plasma was carried out by affinity chromatography. For this purpose, desAA-fibrin and fibrinogen immobilized on Sepharose 4B were used at the stationary side whereas batroxobin-induced 125I-desAA-fibrin or thrombin-induced 125I-desAABB-fibrin mixed with plasma containing 131I-fibrinogen represented the fluid phase. The binding characteristics of these mixtures to the immobilized proteins were compared at 20° C and 37° C. Complete binding of both types of fibrin to the immobilized desAA-fibrin was always seen at 20° C as well as at 37° C. However, binding of soluble fibrin was accompanied by substantial binding of fibrinogen that was more pronounced at 20° C. Striking differences depending on the temperature at which the affinity chromatography was carried out, were documented for the fibrinogen-fibrin interaction. At 20° C more than 90% of the applied desAA-fibrin was bound to the immobilized fibrinogen whereas at 37° C only a mean of 17% were retained at the fibrinogen-Sepharose column. An opposite finding with regard to the tested temperature was made with the desAABB-fibrin. Nearly complete binding to insolubilized fibrinogen was found at 37° C (95%) but only 58% of the desAABB-fibrin were bound at 20° C. The binding patterns did not change when the experiments were performed in the presence of calcium ions. The opposite behaviour of the two types of soluble fibrin to immobilized fibrinogen at the different temperatures, together with the substantial binding of fibrinogen in the presence of soluble fibrin to insolubilized fibrin in every setting tested, devaluates affinity chromatography as a tool in the quantitative assessment of soluble fibrin in patients’ plasma.
Keywords: Soluble fibrin; Fibrinogen; Affinity chromatography